Evaluating the effectiveness of chlorhexidine digluconate 7.1% in comparison to alternative cord care practices in Kiambu County, Kenya: A cross-sectional study on neonatal outcomes - James Maina Githinji; Angeline Chepchirchir; Prabhjot Kaur Juttla; Ruth Nduati (Journal of Interventional Epidemiology and Public Health)
Introduction: The World Health Organization (WHO) recommends chlorhexidine (CHX) for cord care in regions with low hospital delivery rates and high neonatal mortality. Based on this, the Kenyan Ministry of Health (MOH) adopted these guidelines nationwide to improve child survival. However, Kiambu County may not meet the WHO’s criteria for CHX use, and we sought to describe and evaluate the outcomes of cord care practices in Kiambu County. Methods: We conducted a cross-sectional survey, collected data through standardized interviews with mothers of infants attending the 6-week well-child clinic at six high-volume hospitals between August and September 2022. Data analysis was conducted using R version 4.2.1, employing both descriptive and inferential statistics, including bivariable and multivariable logistic regression. Results: We enrolled 434 mothers to participate in the study. CHX cord care uptake was 27.9% in public facilities and 100% in private ones. CHX resulted in a 93.3% healing rate, surgical spirit achieved 96.2%, and dry cord care showed a 100% healing rate. Self-application of CHX was associated with over four times greater likelihood of healing than healthcare-assisted application (adjusted odds ratio [AOR] = 4.24, 95%cCI= 0.0152 – 6.19, p = 0.55). Previous CHX use increased healing odds (COR = 1.16, 95%CI= 0.25-4.13, p = 0.8281), though not statistically significant. Mothers at Kiambu Level 5 hospital, using predominantly CHX, had a 64% lower likelihood of positive outcomes compared to those at Thika Level 5, where dry cord care was common (AOR = 0.36, 95%CI= 0.12-1.01, p = 0.06). Surgical spirit users had 1.85 times higher odds of positive outcomes compared to CHX users, but this was not statistically significant (AOR=1.85, 95%CI= 0.73-5.07, p = 0.20). Conclusion: The study found that cord care practices in Kiambu, such as CHX, dry cord care, and methylated spirit, showed comparable effectiveness. This suggests that the Ministry of Health’s nationwide guidelines for CHX use may need to be reconsidered, especially in regions like Kiambu, where alternative practices may be just as effective. A more context-specific approach, considering local health data and infrastructure, could enhance neonatal outcomes and optimize resource use.